CHARACTERISTICS OF SHRIMP PASTE WITH RED YEAST RICE AS A NATURAL COLORANT: KARAKTERISTIK TERASI UDANG DENGAN ANGKAK SEBAGAI PEWARNA ALAMI - Yuliana, Anna; Pebiansyah, Anisa; Hidayat, Taufik; Fitriani, Windi (Jurnal Teknologi Perikanan dan Kelautan, 2025)
The use of synthetic dyes in food raises various health concerns, so the use of natural dyes as a substitute for synthetic dyes is a safer and more beneficial solution. One potential natural dye is red yeast rice produced by the fungus Monascus sp. This dye is not only safe but also improves the quality of food products. The research aims to determine the optimal concentration of red yeast rice as a coloring agent in the production of shrimp paste. The concentrations of red yeast rice tested include 0.5%, 1%, 1.5%, and 2%. Shrimp paste is made from fresh Acetes sp. shrimp and other shrimp heads with a ratio of 1:1, and is fermented for 20 days. The results showed that the addition of red yeast rice significantly affected the characteristics of shrimp paste, especially in improving color without changing the taste, aroma, and texture. The hedonic test identified that the addition of 2% red yeast rice produced the best product according to the panelists. Shrimp paste products with 2% red yeast rice meet the requirements of SNI 2716:2016 and are most preferred, with an average preference value of 3.27 for shrimp paste with red yeast rice powder and 3.67 for shrimp paste with red yeast rice extract.